2017
DOI: 10.1111/jmi.12557
|View full text |Cite
|
Sign up to set email alerts
|

Fast ‘Operando’ electron nanotomography

Abstract: Electron tomography in transmission electron microscopy provides valuable three-dimensional structural, morphological and chemical information of condensed matter at nanoscale. Current image acquisitions require at least tens of minutes, which prohibits the analysis of nano-objects evolving rapidly such as under dynamic environmental conditions. Reducing the acquisition duration to tens of seconds or less permits to follow in 3D the same object during its evolution under varying temperatures and pressures. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…4c) are routinely possible and that the addition of the homebuilt gas feed and analysis setup to the TEM does not limit the resolution. It should be noted that the spatial resolution is similar to previous reports that have investigated different catalytic systems in situ (Kooyman et al, 2001; Hansen et al, 2002; Allard et al, 2012; Bremmer et al, 2017; Zou et al, 2017; Dembele et al, 2018; Roiban et al, 2018; Altantzis et al, 2019; De Vrieze et al, 2019; Tan et al, 2019). In a first attempt, imaging and diffraction were tested during the in situ synthesis of Pt NPs.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…4c) are routinely possible and that the addition of the homebuilt gas feed and analysis setup to the TEM does not limit the resolution. It should be noted that the spatial resolution is similar to previous reports that have investigated different catalytic systems in situ (Kooyman et al, 2001; Hansen et al, 2002; Allard et al, 2012; Bremmer et al, 2017; Zou et al, 2017; Dembele et al, 2018; Roiban et al, 2018; Altantzis et al, 2019; De Vrieze et al, 2019; Tan et al, 2019). In a first attempt, imaging and diffraction were tested during the in situ synthesis of Pt NPs.…”
Section: Resultssupporting
confidence: 83%
“…MEMS-based nanoreactors allow for pressures up to 14 bar (Creemer et al, 2011) and temperatures up to 1,300°C (Garza et al, 2017). Several in situ TEM studies using MEMS-based nanoreactors have yielded results with different functional materials in various reductive and oxidative environments (Kooyman et al, 2001;Hansen et al, 2002;Giorgio et al, 2008;Vendelbo et al, 2014;Crozier & Hansen, 2015;Aouine et al, 2016;Bremmer et al, 2017;Zou et al, 2017;Dembele et al, 2018;Roiban et al, 2018;Altantzis et al, 2019;De Vrieze et al, 2019;Tan et al, 2019). Although most of these studies are not directly proofing the catalytic function, they still provide valuable information about structural and morphological changes of materials in various gas atmospheres at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Once formed, the particle is usually too large to pass through the zeolite shell and the yolk–shell composite can be calcined or reduced at high temperature without any changes in the particle size. In the particular case of Ag, in situ environmental TEM observations of TPA + ‐containing hollow crystals heated under O 2 atmosphere showed that nanoparticles disappeared at 450 °C, which corresponds to the temperature of decomposition of organic molecules . Decomposition of organic molecules liberates the porosity of the zeolite and enables oxygen to penetrate the cavity and oxidize Ag NPs.…”
Section: Applications: Encapsulation Methodsmentioning
confidence: 99%
“…A major drawback of electron tomography is the time needed to acquire a full tomographic tilt series, which will hamper the investigation of fast processes in 3D. 28 In addition, long exposure times may cause undesired changes within the NPs, making it difficult to differentiate between heat-induced and electron beam induced changes. Therefore, one of the emerging challenges in the field of electron tomography is to improve the speed of tomography experiments, while preserving the quality of the 3D reconstructions.…”
Section: Introductionmentioning
confidence: 99%